Needle exchange decreases the prevalence of HIV-1 proviral DNA in returned syringes in New Haven, Connecticut. - Heimer, R; Kaplan, E H; Khoshnood, K; Jariwala, B; Cadman, E C (The American journal of medicine, 1993)
To report on the deployment of the syringe tracking and testing system in the New Haven needle exchange program, which is the first federally funded evaluation of a needle exchange program conducted in the United States.
Keywords: Analysis of Variance; Connecticut; DNA, Viral; HIV Infections; HIV-1; Humans; Needles; Prevalence; Program Development; Public Health Administration; Substance Abuse, Intravenous; Syringes